Specific Issues of Legal Responsibility for Corruption Offenses in Ukraine - Inna KULCHII; Iryna PASICHNA; Volodymyr ZADOROZHNYY (Communications of International Proceedings, 2020)
The purpose of the article is to study the problems of legal responsibility for corruption offenses in Ukraine, the distinction between corruption crimes and corruption offenses and the application of appropriate disciplinary liability for their commission in order to improve the anti-corruption legislation of Ukraine. General dialectical method and special theoretical research methods are used in the article. In particular, the dialectical method is used to understand the nature of the types of legal responsibility for corruption offenses; scientific abstraction – defining signs and characteristics of corruption crime as a type of offenses; system analysis – establishing the systemic nature of anti-corruption activities; comparative analysis – determining the correlation between corruption crimes and corruption offenses; statistical methods - used in the analysis of the level of corruption in Ukraine according to the Corruption Perceptions Index. The analysis of the status of corruption and anti-corruption activities in Ukraine showed that the main problems of legal responsibility for corruption offenses are related to insufficient judicial practice, lack of prudent regulatory policy, disadvantages of Ukrainian anti-corruption laws, which needs improvement. Solving these problems is to establish tougher measures of responsibility for corruption, and to predict the criminal responsibility for persons who submit false information in their declarations and the application of disciplinary liability in the form of dismissal for committing a corruption crime and a corruption offense under administrative law. It will reduce the number of offenses related to the submission of declarations with false information and in general reduce the level of corruption in Ukraine.
Keywords: Ukraine; corruption; offense; legal responsibility.